Demografi Politik pada Pemilukada Provinsi Sumut Tahun 2013 di Kota Medan - T IRMAYANI (Politeia: Jurnal Ilmu Politik, 2015)
This study examined how voters map to see the map of demographics population in the regional election in Sumatera Utara Province In 2013, the main focus of this study is looking at how the composition of the population in the city of Medan based on differences in ethnicity, gender, education, and work in each District of the sample. This study becomes important in terms of the academic study of political preferences crew community Medan is the actual discussion re-lated to urban society and the rationality of voters as an indicator of the quality of the demo-cratic system that runs in the area. This subject also related to the dynamic nature of social and cultural life of society, in which the dynamics determine how the process of development of a region. This study is using political behaviour as the approach and the data collection is using field research.Keywords: Election, governor, demographic.